Pengaruh Material Abu Batu Basalt, Semen, dan Pasir pada Peningkatan CBR Tanah Lempung untuk Stabilisasi Jalan - Pujiastuti, Heni; Maya Saridewi Pascanawaty; Cita Santuni (Mataram University, 2025)
Soft clay often has poor mechanical properties for structures, including relatively low bearing capacity and a relatively large settlement. To increase the bearing capacity of clay, stabilization with a mixture of cement, sand, and basalt ash is necessary. The research was conducted in the laboratory of the University of Muhammadiyah Mataram. Soil samples were taken from Keruak Village, Keruak District, East Lombok Regency. Variations of cement mixture (SP) + sand (PS) + basalt ash (AB) were respectively 5% + 15% + 3%, 5% + 15% + 6% and 5% + 15% + 9%. Furthermore, soil physical properties testing, Proctor standard compaction test, and CBR test were conducted. From the Proctor compaction test, the optimum water content of the original soil was 32.80%. The mixture with a variation of 5% + 15% + 3% optimum water content was 31.20%, for 5% + 15% + 6% it was 30.90%, and 5% + 15% + 9% it was 30.00%. The results of the unsoaked CBR test on the unstabilized soil were 10.68%, and the soaked CBR value was 3.97%, if used as a subgrade for dirt roads, it must be stabilized first. From the three variations of the mixture above, the optimum CBR variation was obtained in the 5% S + 15% P + 6% ABB mixture, which was 13.58% or an increase in the CBR value of 27.153%. The CBR results with the mixture of 5%S+15%P+6%ABB can be used to stabilize clay soil.